IRREGULAR MIGRATION, CROSS BORDER CRIME AND THE SECURITIZATION THEORY: A SOUTH AFRICAN REFLECTION - Mlambo, Victor H (Journal of Social Political Sciences, 2021)
This paper attempted to examine the narratives and debates around Undocumented migration, cross border crime and the securitization and militarization of South Africa’s borders. Adopting a systematic review of literature, this paper attempted to add to the growing literature around this highly politicized issue. This paper revealed that Undocumented migration and cross border crime are not serious issues that pose a threat to the country's socio-economic development let alone its national security. The drive to securitize these issues has been driven by politicians who seek voters and who use migrants as political scapegoats. This paper contends that rather than investing millions on border securitization and militarization, such monies will be well spent on health, education, social welfare and infrastructure development. Finally, this paper argues that unilateral approaches to border security are bound to fail because the factors driving Undocumented migration and cross border crime are multifaceted and beyond South Africa's control. Hence regional cooperation becomes key. Securitization and militarization approaches don’t stop migration and border crime, rather migrants and crime syndicates always find ways to go around such approaches.